Health economics and policy - Henderson, James W . (Thomson Learning, 2007)
This text is a basic introduction to the microeconomics of health, health care, and health policy. Its main goals are to: demonstrate the application of economic principles to health-related issues; explain the social, political, and economic contexts of health care delivery; explore the changing nature of health care; and analyze public policy from an economic perspective. Contents same as US/UK editions.